DIGITAL TRANSFORMATION OF THE BANKING SYSTEM OF UKRAINE - SYDORCHUK, Ivanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the current issues of digitalization of the banking sector of Ukraine in the context of modern trends. The key prerequisites for the active implementation of digital technologies in the domestic banking system are analyzed, and the main innovative tools that are changing the global banking landscape are described in detail. In particular, attention is paid to such technologies as artificial intelligence, machine learning, Blockchain. Modern solutions are considered, in particular biometric authentication, encryption and tokenization, which help banks protect customers' personal information. The emphasis is on summarizing the main advantages and potential challenges that accompany the digital transformation of traditional banking institutions. The impact of these changes on both the functioning of banks and interaction with their customers through the main functions of digital applications of Ukrainian banks is considered.Innovative tools help automate workflows, significantly reduce costs, and ensure increased transaction security. For example, implementing AI in banking to analyze credit risks can significantly reduce the share of loan defaults, speed up decision-making, and improve their quality. Blockchain technology provides a high level of transparency and traceability of all financial transactions by storing each transaction in an open ledger. This mechanism allows banking institutions to exercise operational control over financial flows directly in real time. Today, banks that provide convenient and secure electronic services gain a competitive advantage in attracting new customers and retaining those who already use their services. Such solutions open up opportunities for market expansion.  A further strategic direction for the development of the banking system in Ukraine is the digitalization of complex banking products, such as mortgages and auto insurance.
Keywords: digitalization; online banking; artificial intelligence; blockchain; tokenization; risks; security